Reducing Rework in Automotive Software through Simulation-Guided Verification - Pestana, Larissa; Miranda, Breno (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
The development of automotive software predominantly follows the V-cycle, where each development phase has a corresponding verification phase. However, integration verification, which considers system complexity, only occurs at the end of the cycle. This results in a disparity between software verification and system verification, where functionally validated code during development becomes dysfunctional during system verification. The lack of adequate preparation leads to significant rework, with algorithm errors being identified only at the end of the cycle, delaying the transition from development to the initial phase of the V-cycle and increasing both costs and time. This research initially explores multiple verification approaches. After analyzing their relevance to the addressed issue, the focus is placed on Simulation-Guided Verification, which has the potential to transform the V-cycle into a W-cycle or V-INC (Verification Incremental Cycle), by inserting in-loop verifications at each development phase. Techniques such as Model-in-the-Loop (MiL), Software-in-the-Loop (SiL), Processor-in-the-Loop (PiL), Hardware-in-the-Loop (HiL), and Virtual-in-the-Loop (ViL) are employed for continuous and iterative verifications, ensuring early fault detection and significantly reducing rework, thereby enhancing the efficiency of automotive software verification.